A practical approach to use the thermodynamic efficiency method for flow measurements. (October 2018) - Lanzersdorfer, J.; Hackl, B.
Abstract: The thermodynamic efficiency method represents the most accurate technique to measure the efficiency of hydraulic machines exceeding 1 kJ/kg of specific energy. On large-scale machines, it is common to use this method also to measure the discharge by simultaneous measurement of the mechanical power. This is either done iteratively or by the use of analytical solutions for simple test setups. We present here an extension of these analytical solutions to arbitrary test setups and conditions, which appear in practical applications. A sign convention has been introduced to harmonize relevant test codes, which deal with performance testing of hydraulic turbines and pumps, in the future. Abstract : Highlights: A sign convention has been introduced for mass flow and for power, which can be exchanged between the reference zone of a hydraulic machine with the environment. The mass flow rate of a fluid can be determined analytically by using thermodynamic method and power measurement. A set of analytical functions based on a generalized test setup could be derived.